Relationship Between Participation In Sport Physio Study Club With Sports Physiotherapy Course Values In Physiotherapy Students Of Universitas Muhammadiyah Surakarta - Arif Pristianto; Khairunnisa Pebriana; Adnan Faris Naufal (JURNAL KEPERAWATAN DAN FISIOTERAPI (JKF), 2022)
There are various forms of active lerning, one of which is interest-based and is called Study Club. In Physiotherapy department Universitas Muhammadiyah Surakarta, There is a Study Club that can help learning in a comprehensive sports physiotherapy course namely Sportphysio. The purpose This study was to determine the relationship in the participation of the Sportphysio study club to the comprehensive sports physiotherapy course in the Physiotherapy study program, Muhammadiyah University of Surakarta. The research used analytic observational, questionnaire distribution, filling was done using google form. This study used a simple correlation test, the chi square test. Sampling with purposive sampling technique, the study used a sample of the batch 2015, 2016 and 2017 physiotherapy students as many as 120 students. Students who already have a Study Result Card for Comprehensive Sports Physiotherapy course are divided into two groups, namely 60 students who take part in the study club and 60 students who do not join the study club, comparing the two groups. The results of the analysis of the chi square test showed that p0.011 had a significant relationship in the participation of the Sportphysio study club with the results of the Comprehensive Sports Physiotherapy course score. The results show that there is a relationship between the participation of the Sportphysio study club and the results of the Comprehensive Sports Physotherapy course scores. The hypothesis is accepted that there is a positive relationship, with the results of students who take part in the Sportphysio study club having good scores, compared to students who don't take part in the Sportphysio study club.